Influence of Interpersonal Relationships on Job Satisfaction through Organizational Culture at PT. PLN (Persero) Rayon Lamongan - Anggraini Enna Np (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
PT PLN (Persero) Rayon Lamongan is one of the state institutions engaged in electric power. Where its operational activities require competent workers, therefore human resource management must also be improved. In this case the interaction between superiors and subordinates as well as employees with employees must be well established. When the relationship between individuals in the work environment has been carried out properly, within the company or agency, an organizational culture will be created that will distinguish the company from other companies. Habits that are carried out continuously and can be accepted by every individual in the company will have an impact on job satisfaction. The research used is a quantitative approach research model by collecting data in the form of numbers. The sample used as many as 64 respondents using a sampling technique that is a saturated sample. This study uses data analysis of validity test, reliability test, normality test, linearity test, and path analysis with the aim of knowing the direct and indirect effect of interpersonal relationship variables on job satisfaction through organizational culture. The results showed that there was no direct influence of Interpersonal Relationships on Job Satisfaction. Meanwhile, there is an indirect influence on Interpersonal Relations on Job Satisfaction through Organizational Culture.